Republic of Moldova : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper reviews Moldova's Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, and Banking Supervision. Compliance with the Basel Core Principles and the IMF Code of Good Practices on Transparency in Monetary and Financial Policies was found to be good with many of the principles, although implementation is sometimes less so. Banks are the most developed part of the financial system. Quantitative indicators of financial soundness are at impressive levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet